Effect of breast cancer education based on the health belief model on knowledge, health belief, and breast self-examination among female students of Debre Markos University, Northwest Ethiopia, in 2021 - Wondmu, Kumlachew Solomon; Tessema, Mekuanint Taddele; Degu, Genet; Mihiret, Getachew Tilaye; Sinshaw, Melkam Tesfaye (Frontiers in Oncology, 2022)
Background Breast cancer is the primary cause of mortality in female patients around the world and the second most common cancer after lung cancer in both sexes. Socio-cultural factors contribute to the development, maintenance, and change of health behavior; knowledge, attitudes, and motivation are important individual determinants of health behavior change. Therefore, this study aims to evaluate the effect of health belief model-based breast cancer education on knowledge, health belief, and breast self-examination among female students of Debre Markos University, Ethiopia, in 2021. Methods A quasi-experimental study was conducted on 210 samples selected by simple random sampling; samples were assigned to an intervention group and a control group based on their cluster. Data were collected by self-administration questionnaire before and after intervention and then entered into Epi data version 3.1 and analyzed by SPSS version 25. A dependent t-test and an independent t-test were used. Difference in difference was used to assess the effect of the intervention. Results Statistically significant differences were observed between groups’ knowledge about breast cancer after educational intervention; monthly breast self-examination practice changes from 20.0% to 57.58% and 17.14% to 24.27% in intervention and control groups, respectively; and average scores of all health belief model constructs show a statistically significant change in the intervention group relative to controls after intervention. Overall knowledge increased by 6.24, perceived susceptibility increased by 4.67, perceived seriousness increased by 6.93, benefit of breast self-examination increased by 3.51, self-efficacy increased by 9.45, cues for action increased by 2.74, barriers of breast self-examination decreased by 3.61, and breast self-examination increased by 2.26 due to educational intervention. Conclusion The health belief model-based education is an effective and efficient way to enhance students’ breast self-examination and promote knowledge and health beliefs about breast cancer. Based on the findings of this study, implementing a health belief model-based educational intervention about breast cancer at different phases of life is important to fight the disease.